Over the hills and far away: phylogeography and demographic migration history of a dispersal-restricted primrose (Primula vulgaris) - Triest, Ludwig; Van Rossum, Fabienne; Sramkó, Gábor; Sierens, Tim; Volkova, Polina (Frontiers in Ecology and Evolution, 2024)
Quaternary glaciations, in particular the last glacial maximum (LGM), have shaped the contemporary distribution of many species. In Europe, survival of temperate species during range contractions was mainly associated with refugia in Mediterranean peninsulas, allowing south to north recolonization. Additionally, the Ponto-Caspian refugium provided an east to west migration route. Here, we investigated genetic diversity and structure of the dispersalrestricted Primula vulgaris Huds., a temperate herb of supposed Caucasian origin, using 12 highly polymorphic nuclear microsatellite loci to trace the colonization of this species in three European regions. We studied 38 populations, namely an eastern mountainous region (Caucasus), a central region (Carpathian Mountains and Dinaric Alps) and a western lowland region (North European Plain). We found the eastern and central regions featuring the highest allelic richness and genetic differentiation being strong between and within regions. Stepwiselike mutation processes (RST > FST), together with isolation-by-distance patterns, contributed to genetic differentiation. The role of an eastern refugium of the species was tested by performing Approximate Bayesian computation analyses to elucidate its demographic and phylogeographic history, detecting bottleneck and expansion events, and estimating effective (ancestral and current) population sizes and time of divergence. Demographic event models showed that P. vulgaris experienced bottlenecks as well as expansions across its range during the Quaternary glacial cycles, with the last expansion about 6,000, 4,000, and 2,000 generations ago for eastern, central, and western populations, respectively. The best supported origin model pointed to the Caucasus population being closest to an ancestral situation, and from where central and western populations diverged subsequently. Divergence time of the Caucasus populations from an ancestral lineage referred to the Upper Pleistocene (Middle Weichselian). Divergence of Carpathian populations, including a Lower Danube valley corridor, was estimated during and across the LGM (Late Weichselian), confirming central populations as potential secondary cryptic refugium. Western populations recently diverged during the Holocene, most probably in the Atlanticum phase (7,000-3,900 years ago). Within regions, genetic structure was also shaped by latitude, longitude, or altitudinal migration, and for western lowlands, by recent bottleneck and genetic drift processes.